PEMANFAATAN MEDIA VISUAL TERHADAP PEMBELAJARAN TEMATIK KELAS III DI MI TARBIYATUS SHIBYAN PETUNG - Fannia Laily Fauziyah; Muhammad Sulistiono; Ika Ratih Sulistiani (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
Learning media serves as an effort to improve the quality of education. In addition, the use of creative, innovative and interesting learning media will also enable students to learn better and will have a good impact on student learning outcomes so that learning objectives can be met. This research was conducted in MI. Tarbiyatus Shibyan Petung Panceng Gresik which is intended to answer questions 1). How to plan the use of visual media in class III thematic learning at MI. Tarbiyatus Shibyan petung. 2). How is the implementation or application of the use of visual media in class III thematic learning at MI. Tarbiyatus Shibyan petung. 3). How are the results of using visual media in class III thematic learning at MI. Tarbiyatus Shibyan petung. This study uses descriptive qualitative research methods, using interviews, observation and documentation. The results of the research conducted indicate that the use of visual learning media greatly influences student learning outcomes because students can more easily understand the material presented by the teacher through learning media.